Diagnosis of the vegetation cover in the wetlands of La Caimanera Swamp, Colombia and Casitas Wetland, Mexico by means of Landsat and Sentinel-2A images during last four decades - Gastón Ballut-Dajud; Erick Arturo Betanzo-Torres; Luis Carlos Sandoval Herazo (Results in Engineering)
Coastal wetlands have gained significant attention in recent decades for their role in climate regulation, particularly through carbon sequestration. However, anthropogenic activities, driven by population growth, have led to the degradation of these ecosystems, causing both loss of area and functional decline. This study aims to use remote sensing techniques, specifically Landsat and Sentinel-2 imagery, to compare the vegetation cover of two coastal wetlands over the past four decades. By applying the Normalized Difference Vegetation Index (NDVI) and Normalized Difference Water Index (NDWI), we assess vegetation phenology and estimate changes in cover area through supervised classification. Results indicated that mangroves exhibited high reflectance in the near-infrared band, with red mangroves (Rhizophora mangle) showing higher reflectance than black mangroves (Avicennia germinans). Both species were identified in the wetlands studied. The mangroves maintain their health, as NDVI values are above 0.6, indicating good photosynthetic activity. However, the mangroves in La Caimanera Swamp are older and show signs of senescence. In terms of water content, NDWI positive values ranged from 0.06 to 0.72, reflecting water presence in both wetlands. Finally, it can be said that the mangrove area is preserved and has not suffered significant damage from human activities.